The dimensionality of the epistemic orientation survey and longitudinal measurement invariance for the short form of EOS (EOS-SF) - Ding, Chenchen; Fulmer, Gavin; Hoffman, Lesa; Hand, Brian; Suh, Jee K. (Frontiers in Education, 2023)
The dimensionality of the epistemic orientation survey (EOS) was examined across four occasions with item factor analysis (IFA). Because of an emphasis on the knowledge generation of epistemic orientation (EO), four factors were selected and built into a short form of EOS (EOS-SF) including knowledge generation, knowledge replication, epistemic nature of knowledge, and student ability. To track the stability of the factor structure for each factor of EOS-SF, longitudinal invariance models were conducted. Partial measurement invariance was obtained for each of the four factors of EOS-SF. This study provides an example of ongoing instrument development in the field of applied assessment research.